Barriers to contraceptive use in humanitarian settings: Experiences of South Sudanese refugee women living in Adjumani district, Uganda; an exploratory qualitative study. - Roselline Achola; Lynn Atuyambe; Elizabeth Nabiwemba; Mathew Nyashanu; Christopher Garimoi Orach (PLoS ONE, 2024)
Introduction Contraceptive use can be lifesaving, empowering and cost-effective for women and girls. Access to contraception is still challenging to female refugees due to several barriers including language, low educational level, lack of information, influence by family members, limited income, cultural and religious norms. This study explored barriers to contraceptive use among South Sudanese refugee women living in Adjumani district, Uganda. Methods An exploratory study design using qualitative methods were employed involving women of reproductive age (15-49 years). Purposive sampling was used to select participants for Focus Group Discussions (FGDs) and In-depth Interviews (IDIs) from three settlements in Adjumani district. We conducted four FGDs, each consisting of 8 participants. We also conducted fourteen in-depth interviews (IDIs) with women of reproductive age. The IDI and FGD guides were translated into local languages before they were used to collect data. The interviews were recorded, transcribed verbatim and translated into English. Audio recordings were labeled before being translated back to English. Deductive, team-based coding was implemented, and a codebook developed. Transcripts were entered, and data coded using Atlas ti version 14. Data were analyzed using content analysis to produce the final outputs for the study. Results The study found several challenges to contraceptive use. These included gender dynamics, socially constructed myths on contraceptive use, cultural norms, limited knowledge about contraceptives, men's negative attitudes, antagonism of contraceptive use by leaders and reprisal of women who use contraception. Conclusion The study concluded that there is need for community strategies to break down the barriers to contraception utilization among refugee women. Such strategies should involve men and women alongside gatekeepers to enhance sustainability.